Interpretive autoethnography - Denzin, Norman K.
It is time to chart a new course-, writes Norman K. Denzin in Interpretive Autoethnography, Second Edition . -I want to turn the traditional life story, biographical project into an interpretive autoethnographic project, into a critical, performative practice, a practice that begins with the biography of the writer and moves outward to culture, discourse, history, and ideology.- Drawing on C. Wright Mills, Sartre, and Derrida, Denzin lays out the key assumptions, terms, and parameters of autoethnography, provides a guide to using and studying personal experience, and considers the dilemmas and political implications of textualizing a life. He weaves his narrative through family stories, and concludes with thoughts concerning a performance-centered pedagogy and the directions, concerns, and challenges for autoethnography.